INTERNALISASI NILAI PANCASILA DALAM PEMBELAJARAN MELALUI PENERAPAN PROFIL PELAJAR PANCASILA BERBANTUAN PLATFORM MERDEKA MENGAJAR (Jurnal Teknodik, 2021)
Salah satu tantangan bagi dunia pendidikan saat ini  adalah bagaimana mengembangkan pendidikan karakter bagi  siswa selama masa new normal. Kemendikbudristek menetapkan  6 indikator dari Profil Pelajar Pancasila. Guna mempermudah  internalisasi Profil Pelajar Pancasila dalam pembelajaran baik oleh  guru maupun siswa, dikembangkan Platform Merdeka Mengajar  (PMM). Penelitian ini bertujuan untuk mengetahui penerapan  pemanfaatan Platform Merdeka Mengajar dalam menginternalisasi  nilai-nilai Pancasila. Sampel penelitian adalah guru-guru sekolah  penggerak dan SMK Pusat Keunggulan yang telah mengikuti bimtek  PMM tahun 2021. Pengumpulan data menggunakan kuesioner,  observasi dan wawancara terbatas. Hasil penelitian menunjukkan  bahwa: 1)Profil Pelajar Pancasila pada hakikatnya merupakan salah  satu upaya internalisasi nilai-nilai Pancasila dalam pembelajaran,  2) PMM memiliki peran signifikan dalam penerapan Profil Pelajar  Pancasila pada pembelajaran paradigma baru, dan 3) Internalisasi  nilai-nilai Pancasila dalam penerapan Profil Pelajar Pancasila di  masa new Normal berbantuan Platform Merdeka Mengajar dengan  cara diterapkan dalam karakter keseharian yang dibangun dan  dihidupkan dalam diri individu setiap pelajar melalui budaya sekolah,  pembelajaran intrakurikuler, kokurikuler, maupun ekstrakurikuler di  sekolah. Peningkatan pemanfaatan Platform Merdeka Mengajar  dalam menginternalisasi nilai-nilai Pancasila melalui Profil Pelajar  Pancasila, perlu didukung dengan upaya peningkatkan kualitas dan  kuantitas konten Profil Pelajar Pancasila serta dukungan kebijakan  dalam pemanfaatan PMM dan sinergi kolaborasi antara sekolah,  pemerintah, masyarakat serta pemangku kepentingan. PMM dapat  menjadi salah satu solusi dalam penguatan pembelajaran karakter  melalui internalisasi nilai Pancasila bagi siswa generasi milenial,  terutama pada saat pembelajaran tatap muka terbatas di masa new normal pandemi Covid-19.One of the challenges in education today is student  character education during the new normal era. The Ministry of  Education, Culture, Research, and Technology sets 6 indicators of  the Pancasila Student Profile. To enhance the internalization of the  Pancasila Student Profile in learning by both teachers and students,  the Merdeka Mengajar Platform (MMP) is developed. The objective  of this research is to know the implementation of MMP in internalizing  the values of Pancasila. The sample is teachers of driving schools  and Center of Excellence Vocational Schools who have participated  in the PMM technical guidance in 2021. Data collection is through  questionnaires, observation, and limited interviews. The result  show that: 1) Pancasila Student Profile is essentially an effort to  internalize Pancasila values in learning; 2) MMP has significant  roles in the implementation of the Pancasila Student Profile in the  new learning paradigm; and 3) The internalization of Pancasila  values in the implementation of Pancasila Student Profile in the  new normal era with MMP is applied in daily characteristics that are  developed and enhanced in every student through school culture,  intra-curricular, co-curricular, and extra-curricular learning at school  by applying it to the daily character that is built and brought to life in  each student through school culture, intra-curricular, co-curricular,  and extra-curricular learning at school. The improvement of MMP  implementation in internalizing Pancasila values through Pancasila  Student Profile should be supported by increasing the quality as well  as quantity of Pancasila Student Profile contents, by policies in MMP  implementation, and collaboration between schools, government,  and other stakeholders. MMP can be one of the solutions to enhance  character education through the internalization of Pancasila values  for millennial students, especially during the limited face-to-face  learning in a new normal era of pandemic covid-19